2004
DOI: 10.1177/089875640402100303
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of an Infrabony Pocket in an American Eskimo Dog

Abstract: This case report describes the use synthetic bone graft particulate and 24% EDTA gel to treat an infrabony defect adjacent to the mandibular right first molar tooth in an American Eskimo dog. Postoperative examination 33-months following surgery showed osseous integration at the infrabony defect and restoration of the periodontal ligament space with a small refractory periodontal pocket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…11,12,20,24 Several veterinary publications have reported successful radiographic periodontal bone regeneration using the bioglass product b without a membrane although the results were not confirmed histologically. 1,[25][26][27] Results of a recent human clinical study suggest that there is increased inhibition of epithelial apical migration using membranes compared with bioactive glass alone. 28 Additionally, a human literature meta-analysis concluded that membranes in general, when combined with any type of bone graft, result in greater clinical attachment levels.…”
Section: Step-by-stepmentioning
confidence: 99%
“…11,12,20,24 Several veterinary publications have reported successful radiographic periodontal bone regeneration using the bioglass product b without a membrane although the results were not confirmed histologically. 1,[25][26][27] Results of a recent human clinical study suggest that there is increased inhibition of epithelial apical migration using membranes compared with bioactive glass alone. 28 Additionally, a human literature meta-analysis concluded that membranes in general, when combined with any type of bone graft, result in greater clinical attachment levels.…”
Section: Step-by-stepmentioning
confidence: 99%
“…In both reports, this bioactive bone graft was used to successfully treat interproximal periodontal defects. 21,22 Bioactive glass (Consil) w and DFDBA appear to be the most commonly used grafting materials in veterinary dentistry. Both products have been shown to clinical improve infrabony periodontal defects by increased attachment levels and bone reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Both products have been shown to clinical improve infrabony periodontal defects by increased attachment levels and bone reconstruction. 9,[20][21][22] While bioactive glass has no risk of disease transmission and an unlimited supply, they are primarily osteoconductive and lack the bone inductive proteins of DFDBA. 15,23 In one study, DFDBA may statistically significantly improve the quality of bone reconstruction in infrabony periodontal defects.…”
Section: Discussionmentioning
confidence: 99%
“…17 Another previously published report on the treatment of a similar defect in a dog using a bone graft revealed successful results without the use of a barrier membrane. 18 In this particular case, doxycycline impregnated in an absorbable polymeric carrier was the barrier membrane of choice based on accessibility of the product at our hospital as well as recent studies evaluating the effect of polylactic acid bioabsorbable membranes for treating infrabony defects in people. 19,20 Doxcycline has also been shown to have an anti-inflammatory effect through the inhibition of matrix metalloproteinases 8 and 12, which are collagen and elastin cleaving enzymes.…”
Section: Discussionmentioning
confidence: 99%